Level of Awareness on Disaster Risk Preparedness in Informal Settlements of Nyeri Town, Nyeri County, Kenya. - Muriuki , Zachary K.; Kei , Robert Kei; Muchiri, John Munderu (International Journal of Health Sciences, 2022)
Purpose: The main objective of this study was to assess level of awareness on disaster risk preparedness in informal settlements of Nyeri town, Nyeri County, Kenya. To achieve this, the study was guided by two specific objectives: to establish the level of awareness on the types of disasters that can affect the informal settlement residents in Nyeri town and to determine the level of awareness on the existence of disaster risk reduction policies to curb disasters among the people living in informal settlements of Nyeri town. Methodology: The study adopted a descriptive research design using primary data collected through a structured questionnaire. The population for this study was 384 respondents of the four settlements of Nyeri town, that is, Majengo Witemere Ngangarithi,mathari and Ruring'u Muslim village. Results: The study found out that, majority of the respondents 93.0% was aware of the disasters that can affect them in their area of residents. The study further established that, majority of the residents 196 (51.0%) was aware of the existence of disaster risk reduction policies as compared to 49.0% who were not aware of any disaster risk reduction policy. The results also showed that there was a significant association between the level of education of the respondents and the level of awareness of the disaster that could affect them [X2 (3) = 14.848, p-value =0.002<0.05] and the religions of the respondents and the level of awareness of the disaster that could affect them [X2 (2) = 7.090, p-value =0.029<0.05]. The results however indicated that, there was no significant association between the level of awareness of the disaster that could affect the respondents with the area of residents, age of the respondents and their occupation as given by the p-values of 0.393, 0.485 and 0.390 respectively. The study further established that, there was a significant association between the education level of the respondents and the level of awareness of any policy rule concerning with disaster risk reduction [X2 (3) = 8.056, p-value =0.045<0.05], and the religions of the respondents and the level of awareness of any policy rule concerning with disaster risk reduction [X2 (2) = 10.031, p-value =0.007<0.05]. Unique Contribution to Theory, Policy and Practice: It was concluded that Risk assessment as a step for successful disaster reduction measures will ensure that the community members are aware of the possible hazards. National and County government should incorporate the national and international policies and guidelines in their policy. The Government should be keen on learning on previous disasters that have affected other informal settlements and other parts of the country by having disaster management well kwon by the communities living in informal sectors. The researcher further recommends to the scholars to consider research on Disaster risk preparedness as the strategy of counties development agenda and Social and economic potentials that the County Governments can tap in informal settlements.